EXPERIMENTAL FOUNDATION OF RADIOFREQUENCY ABLATION OF MYOCARDIAL TISSUE FOR MAZE OPERATIONS IN THE OPEN HEART - Sychyk, M. M.; Maksymenko, V. B.; Kravchuk, B. B.; Lafeta, O. O. (Visnyk of Vinnytsia Politechnical Institute, 2016)
The work is devoted to research of interrelations of separate influence of radiofrequency energy power and electrode temperature to the destruction size of heart areas for using two lengths of electrodes. Effective and safe modes and parameters radiofrequency ablation were designated. Practical implementation of the results of experimental studies reduced the size of the heart tissue destruction at the effective elimination of arrhythmias. Minimum necessary and sufficient characteristics of RF power and temperature influence to correct arrhythmias during surgery Maze were defined.